Percutaneous Device Closure of Congenital Isolated Ventricular Septal Defects: A Single-Center Retrospective Database Study Amongst 412 Cases - Walavalkar, Varsha (Pediatr Cardiol, 2020)
To identify suitable cases and reduce failure/complication rates for percutaneous ventricular septal defect (VSD) closure, we aimed to (1) study causes of device failure and (2) compare outcomes with different VSD types and devices in a high-volume single center with limited resources. Retrospective data of 412 elective percutaneous VSD closure of isolated congenital VSDs between 2003 and 2017 were analyzed. Out of 412, 363 were successfully implanted, in 30 device implantation failed, and in 19 the procedure was abandoned. Outcome was assessed using echocardiography, electrocardiography, and catheterization data (before procedure, immediately after and during follow-up). Logistic regression analyses were performed to assess effects of age, VSD type, and device type and size on procedural outcome. Median [interquartile range] age and body surface area were 6.6 [4.1–10.9] years and 0.7 [0.5–1.0] m(2), respectively. Device failure was not associated with age (p = 0.08), type of VSD (p = 0.5), device type (p = 0.2), or device size (p = 0.1). Device failure occurred in 7.6% of patients. As device type is not related to failure rate and device failure and complication risk was not associated with age, it is justifiable to use financially beneficial ductal devices in VSD position and to consider closure of VSD with device in clinically indicated children.